Strategi Pembelajaran True Or False Dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran Aqidah Akhlak - Erda Ermawati; Rizda Nirmalasari; Yayuk Primawati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research aims to improve student learning outcomes by using a true or false strategy. This type of research is classroom action research. Data collection techniques use observation, documentation, interviews and tests. The data analysis technique uses quantitative data analysis with simple statistics and classroom action research procedures using 2 cycles of the Kurtlewin model. This research was able to obtain learning results in cycle I of 58.33%. After reflection, learning activities in cycle II became 83.33%, resulting in an increase of 25%. Then, the percentage of students who completed cycle I was 59.02% and students who completed cycle II was 77.08%, resulting in an increase of 18.06%.